Mortality in the first 24h of very low birth weight preterm infants in the Northeast of Brazil - Eveline Campos Monteiro de Castro; Álvaro Jorge Madeiro Leite; Ruth Guinsburg (Sociedade de Pediatria de São Paulo, 2016)
Abstract Objective: To evaluate factors associated with neonatal death within 24 hours after birth in very low birth weight preterm newborns. Methods: Prospective cohort of live births with gestational age of 230/7-316/7 weeks, birth weight of 500-1499g without malformations, in 19 public maternity hospitals in nine capitals in northeastern Brazil from July to December 2007. The 19 hospitals were assessed in relation to physical resources, equipment, human resources and aiming at quality in care initiatives. Hospital, maternal and neonatal characteristics, neonatal morbidity, neonatal procedures and interventions were compared between preterm newborns that died or survived up to 24 hours of life. The variables associated with death within 24 hours after birth were determined by logistic regression. Results: Of the 627 newborns enrolled in the study, 179 (29%) died within 168 hours after birth, of which 59 (33%) up to 24 hours and 97 (54%) up to 48 hours after birth. The variables associated with death <24h were: weight <1000g (2.94; 1.32-6.53), 5th minute Apgar <7 (7.17; 3.46-14.88), male gender (2.99; 1.39-6.47). A better hospital structure was a protective factor for early neonatal death (odds ratio: 0.34; 95% confidence interval: 0.17-0.71). Conclusions: The high neonatal mortality on the first day of life in capital cities of Northeast Brazil is associated with biological variables such as weight and gender of the newborn, as well as low vitality at birth and a worse infrastructure of the hospital where the birth occurred.